Banco Popular : Equity Research - Gonçalves, João Miguel Martins (2013)
There are several valuation methods available for equity research; their suitability varies with each specific company’s characteristics. The objective of this dissertation is to choose from the existing methods, the one which is more appropriate for Banco Popular, in order to come up with a recommendation target price. Finally I will compare my results with those obtained by Bankia in the equity research report published on the 2nd February 2012